Contexte spatial des ambiances urbaines et usage des lieux - Arnaud Piombini (Ambiances)
This paper aims to show a geographical point of view about the spatial organization of ambient environment. The main goal consists to describe several methods of spatial analysis in order to characterize the ambient environment spatial context. A choice model can be used to work on both spatial structure and pedestrian mobility experiences and thereby highlight ambient environment preferences of walkers. The objective is to replace ambient environment in the context of opportunities and constraints that bind townspeople to urban areas and ultimately affect people’s perceptions and uses of places.